Surface modifications by plasma treatment, chemical grafting and over dyeing of polyamide nets to improve the antifouling performance in the aquaculture field. (July 2019) - Amara, Intissar; Miled, Wafa; Ben Slama, Rihab; Chevallier, Pascale; Mantovani, Diego; Ladhari, Néji
Highlights: Biofouling appears on any immersed structure in seawater. It causes many problems on aquaculture fields. Antifouling formulations have been proposed to control the biofouling. They were found to be toxic on different species. PA nets were modified by applying products used in textile field. Dyes with a very low percentage of copper were employed. Nets were modified by grafting technique with Methacrylic Acid and atmospheric air plasma treatment. The evaluation towards the accumulation of bacteria and algae was done by using physical and biological techniques.